A review of in vitro approaches as tools for studying rumen fermentation and ecology: effectiveness compared to in vivo outcomes - Federica Scicutella; Giulia Foggi; Matteo Daghio; Federica Mannelli; Carlo Viti; Marcello Mele; Arianna Buccioni (Italian Journal of Animal Science)
In vitro methods offer valuable insights into feed fermentations, composition, and function of ruminal microbiota, providing evaluations under standardised conditions, at lower costs than in vivo trials, minimising the reliance on live animals. However, studies comparing in vitro and in vivo approaches are limited. Therefore, this review aims to stimulate a critical discussion on the use of in vitro trials as an investigative tool in animal nutrition. The in vitro trial methodologies are analysed at different levels to highlight advantages and limitations of their application: I) rumen liquor collection; II) main typologies of in vitro fermentation; III) essential differences between in vitro and in vivo systems, including the application field; IV) critical analysis of in vitro vs in vivo, targeting specific ruminal biomarkers (e.g. fatty acids, microbiota). Overall, the comparability of data from in vitro and in vivo studies is limited. This can partly be attributed to factors occurring before the fermentation, such as rumen liquor collection methodology or fermentation system chosen. Contamination with saliva can increase pH, and different feed-to-RL ratio affects fermentation extent. The absence of rumen walls, the lack of stratification of feed material, and microbiota-host interaction restrict the representativeness of ruminal microbiota communities in vitro. Despite these challenges, in vitro experiments have provided data that could not be obtained in vivo and have enabled focusing on specific metabolic pathways. Further studies aiming at comparisons of common and targeted properties are needed to enhance and expand the applicability of in vitro studies while considering the inherent limitations.